ANALISA PEMBERIAN JENIS PUPUK ORGANIK DAN PEMASANGAN SUNGKUP TERHADAP PENINGKATAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) - Mariyatul Qibtiyah; Muhammad Nuri; Choirul Anam; Muhammad Imam Aminuddin (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
Onion plant growth is often limited by nutrient availability and environmental influences. In addition, the use of hoods as a plant protection technique is expected to create microenvironmental conditions favorable to growth. The purpose of the study was to assess the effectiveness of using various kinds of organic fertilizers and the application of hoods in increasing shallot production. Factorial Randomized Group Design (RAK) was used, which consisted of two factors. The first factor was the type of organic fertilizer, namely bokashi fertilizer, guano fertilizer, and cow fertilizer. The second factor was the hood, namely control, waring hoods, and plastic hoods. Observation parameters observed in the vegetative phase consisted of: number of leaves, plant height. While the generative phase consisted of: number of tubers, wet weight of tubers per sample, wet weight of tubers per plot, dry weight of tubers per sample, and dry weight of tubers per plot. The results of variance analysis showed significant differences in the parameters of plant height at 14, 21, 28 days, and the number of leaves at 14, 21 days. In all parameters observed, the hoods treatment in the generative phase showed no significant results. The results of the study obtained that the treatment of guano fetilizer without a hoods produced the best tuber weight.